Milled flake graphite/plasma nano-silicon@carbon composite with void sandwich structure for high performance as lithium ion battery anode at high temperature. (April 2018) - Chen, Hedong; Hou, Xianhua; Chen, Fuming; Wang, Shaofeng; Wu, Bo; Ru, Qiang; Qin, Haiqing; Xia, Yingchun
Abstract: To reduce the influence from volume expansion of silicon during lithium lithiation/delithiation, milled flake graphite/plasma nano-silicon@carbon (MFG/PNSi@C) composite with void sandwich structure is synthesized by assembling thin MFG (thickness of 150 nm) sheets loading with carbon-coated PNSi (plasma nano-silicon) via a facile spray drying method. The MFG/PNSi@C composite, as lithium ion battery anode, exhibits excellent electrochemical performance at room temperature and displays an outstanding cyclic property even at high temperature. The MFG/PNSi@C electrode delivers reversible capacity of 1141 mAh g −1, and high initial Coulombic efficiency of 84.4%, and capacity retention of 84.1% after 200 cycles at a current density of 0.1 A g −1 . Even at the current density of 0.2 and 0.4 A g −1, the reversible capacities of 1168 and 1102 mAh g −1 can be achieved respectively, with the capacity retention of 68.9% and 63.9% after 200 cycles. Even the work temperature goes up 60 °C, the discharge/charge capacities of 832/808 mAh g −1 can be obtained at a current density of 0.1 A g −1 . The stable cyclic performance is mainly due to the void sandwich structure of the MFG/PNSi@C composite, which dramatically shortens lithium ion diffusion path and pitch carbon shell can buffer huge volume expansion. Graphical abstract: Image